PHILOSOPHICAL VALUES IN NUMBER THEORY OF IKHWĀN AL-ṢAFĀ' - Walid, Kholid Al; Miri, Mohsen; Rijal, Syamsul; Lestari, Ayu; Norman, Nurul Ain (Universitas Islam Negeri Ar-Raniry, 2024)
In mathematics, especially Arithmetic, there is a theory of numbers that can represent philosophical values. Mathematics is often presented with materialist values without deep meaning. One group of classical philosophers with mathematical thoughts, especially number theory, which explains the number material itself and relates it to meaningful philosophical values, is Ikhwān al-Ṣafā'. This research aims to reveal the philosophical values contained in the thought of the number. Using a qualitative research method based on a literature study approach, the researcher specifically examines the phenomenal book Rasā'il Ikhwān al-Ṣafā' as a primary source as well as other relevant references as secondary sources. The study found that in the number theory of Ikhwān al-Ṣafā', there are philosophical values such as monotheism described by the characteristics of the number one and the value of creation described by the sequence of the number ladder. This research initiates a discourse on the philosophy of numbers that previously has never been studied for it will serve as a pioneer for further research.